DO JIGSAW WITH AND WITHOUT EDMODO NEEDED IN TEACH INTEGRATED SKILLS (Reading and Writing)? - Farida Salim (Language-Edu, 2021)
To get good writing skills requires a lot of practice, as well as in the process of producing a paragraph which also requires structured stages. In supporting the writing process, appropriate teaching and learning methods need to assist students master writing skill. In his study, researcher offers alternative methods to measure the  effectiveness  of  writing  narrative  text  using  the  Jigsaw  method  with  Edmodo and  conventional  Jigsaw.  Its  research  design was  quasi-experimental  with  a  non- randomized, pre-post test design. The study was conducted at X Grade Multimedia (MM 1 and MM 2) students of SMK PGRI 2 Kediri in the academic year 2019/2020, consist of 20 students each class. The writer uses the writing test as an instrument in  collecting  data;  and  with  pre-post test  design  form.  The  test  used  to  classify students’ writing ability in relation to the effect of the treatment. Then, an analytic scoring  rubric  used  by  two  raters  worked  independently  in  scoring  the  students’ writing.     The results showed that the mean scores of the three writing components in the experimental group were not significantly different or nearly the same. This is shown  by  statistical  calculations  using  the  Independent  Sample  of  T-test  with  a significant value at the level of 0.145> 0.05. These findings indicate that there is no significant  difference  between  students'  scores  in  learning  using  Jigsaw  with Edmodo and conventional Jigsaw. There was an increase in student scores, but the increase  was  not  too  significant.  These  findings  suggest  that  there  is  insufficient evidence  to  reject  the  null  hypothesis.  Then  the  alternative  hypothesis  is  not accepted.  Students  taught  using  Jigsaw  with  Edmodo  did  not  have  a  significant difference in learning achievement and writing narrative text compared to students who  were  taught  using  conventional  Jigsaw.  Based  on  the  research  finding,  the students taught using Jigsaw with Edmodo do not get a significantly better score in writing narrative text than students taught using Jigsaw conventional. Even though, there is no significant level student score improvement the application jigsaw with Edmodo and Conventional Jigsaw was suggested to English teachers to apply those methods to improve students’ writing skill. The students will be nice when using a media  likes  Jigsaw  and  Edmodo  in  the  teaching-learning  process.  For  future research, writer recommend to fill the gaps of this research limitation as a reference in conducting research both in the same or different field. Keywords: Jigsaw, Edmodo, Writing, Narrative Text     To get good writing skills requires a lot of practice, as well as in the process of producing a paragraph which also requires structured stages. In supporting the writing process, appropriate teaching and learning methods need to assist students master writing skill. In his study, researcher offers alternative methods to measure the  effectiveness  of  writing  narrative  text  using  the  Jigsaw  method  with  Edmodo and  conventional  Jigsaw.  Its  research  design was  quasi-experimental  with  a  non- randomized, pre-posttest design. The study was conducted at X Grade Multimedia (MM 1 and MM 2) students of SMK PGRI 2 Kediri in the academic year 2019/2020, consist of 20 students each class. The writer uses the writing test as an instrument in  collecting  data;  and  with  pre-posttest  design  form.  The  test  used  to  classify students’ writing ability in relation to the effect of the treatment. Then, an analytic scoring  rubric  used  by  two  raters  worked  independently  in  scoring  the  students’ writing.     The results showed that the mean scores of the three writing components in the experimental group were not significantly different or nearly the same. This is shown  by  statistical  calculations  using  the  Independent  Sample  of  T-test  with  a significant value at the level of 0.145> 0.05. These findings indicate that there is no significant  difference  between  students'  scores  in  learning  using  Jigsaw  with Edmodo and conventional Jigsaw. There was an increase in student scores, but the increase  was  not  too  significant.  These  findings  suggest  that  there  is  insufficient evidence  to  reject  the  null  hypothesis.  Then  the  alternative  hypothesis  is  not accepted.  Students  taught  using  Jigsaw  with  Edmodo  did  not  have  a  significant difference in learning achievement and writing narrative text compared to students who  were  taught  using  conventional  Jigsaw.  Based  on  the  research  finding,  the students taught using Jigsaw with Edmodo do not get a significantly better score in writing narrative text than students taught using Jigsaw conventional. Even though, there is no significant level student score improvement the application jigsaw with Edmodo and Conventional Jigsaw was suggested to English teachers to apply those methods to improve students’ writing skill. The students will be nice when using a media  likes  Jigsaw  and  Edmodo  in  the  teaching-learning  process.  For  future research, writer recommend to fill the gaps of this research limitation as a reference in conducting research both in the same or different field. Keywords: Jigsaw, Edmodo, Writing, Narrative Text